Ratcheting up effectiveness to improve the Global Stocktake process - Stringer, L.C.; Dhakal, S.; Milkoreit, M.; Mendoza, C.; Mukherji, Aditi; Shishlov, I.; Fisher, S.; Simpson, N.P.; Schleussner, Carl-Friedrich (Elsevier, 2023)
The Paris Agreement rests on voluntary emissions reduction pledges but does not mandate that pledges are sufficiently ambitious to collectively limit warming to acceptable levels. Instead, it relies on the “ratcheting mechanism” of the Global Stocktake. As the world falls further from emissions trajectories compatible with the Paris Agreement, a safe and just future relies on increased global effort. This Voices asks: what is needed for the Global Stocktake to be a pivotal mechanism for raising climate ambitions and action?